Temporal variation in the effects of impact factors on residential land prices. (January 2020) - Qu, Shijin; Hu, Shougeng; Li, Weidong; Zhang, Chuanrong; Li, Quanfeng; Wang, Hui
Abstract: Understanding the spatiotemporal variation effects of impact factors (IF) on residential land prices (RLP) is an essential requirement for reasonably distributing infrastructure in urban development and renewal. Although many previous studies examined these effects in the dimension of space, temporal variations have been relatively neglected. This study investigated the temporal variation in the effects of IF on RLP from both global and local perspectives by using the spatial econometric model and the geographically weighted regression (GWR) model, respectively. Results showed that the effects of IF on RLP were temporally non-stationary in Wuhan, a city in central China. At the global scale, the IF associated with living quality, including hospitals, parks, waterscapes, and universities, had increasing impacts on RLP from 2004 to 2017 while the contributions of road density and floor-area ratio to RLP showed a decreasing trend. This indicates that residents may incline to a more comfortable living environment when their demands for convenient transportation and commercial service can be satisfied. At the local scale, the effects of environmental amenities (parks and waterscapes) on RLP increased in less developed areas, and such an increase came with improvements in the quality of transportation and commercial services in these areas. This finding suggests that the positive externalities of environmental amenities can be well-reflected in land prices when the amenities are integrated with good infrastructure. This study shows a temporal change of human preferences for infrastructure in a rapidly developing city, Wuhan, providing a valuable reference to urban planners when it comes to the distribution of infrastructures within similar cities. Highlights: Temporal variations in the effects of impact factors on land prices are explored from both global and local perspectives. The effects of impact factors on residential land prices are temporally non-stationary. The coefficients of impact factors associated with living quality have grown significantly from 2004 to 2017. Environmental amenities have a more significant impact on land price after the surrounding infrastructure is improved.